Tejano legacy : rancheros and settlers in south Texas, 1734-1900 - Alonzo, Armando C. (Albuquerque : University of New Mexico Press, 1998)
This is a study of Tejano ranchers and settlers in the Lower Rio Grande Valley from their colonial roots to 1900. The first book to delineate and assess the complexity of Mexican-Anglo interaction in South Texas, it also shows how Tejanos continued to play a leading role in the commercialization of ranching after 1848 and how they maintained a sense of community.
Despite shifts in jurisdiction, the tradition of Tejano landholding acted as a stabilizing element and formed an important part of Tejano history and identity. The earliest settlers arrived in the 1730s and established numerous ranchos and six towns along the river. Through a careful study of land and tax records, brands and bills of sale of livestock, wills, population and agricultural censuses, and oral histories, Alonzo shows how Tejanos adapted to change and maintained control of their ranchos through the 1880s, when Anglo encroachment and varying social and economic conditions eroded the bulk of the community's land base.
Note on Burmese Words Ch. 1. The Myth of a Sinhalese Invasion of Pagan in 1165 A.D. Ch. 2. The "King Who Fled the Chinese" and Disapramok's Mission to China: Two Myths in the History of Pagan Ch. 3. The Destruction of Pagan: the Myth and the History Ch. 4. The Myths Surrounding King Klawcwa, Man Lulan, Kumarakassapa, and Tak To Mu Mankri Ch. 5. The Myth of the Three Shan Brothers.
Includes bibliographical references (pages 301-345) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Lower Rio Grande Valley (Tex.) -- History; Frontier and pioneer life -- Texas -- Lower Rio Grande Valley; Ranchers -- Texas -- Lower Rio Grande Valley -- History; Mexicans -- Texas -- Lower Rio Grande Valley -- History; Land tenure -- Texas -- Lower Rio Grande Valley -- History; Lower Rio Grande Valley (Tex.) -- Ethnic relations; Basse vallée du Rio Grande (Tex.) -- Histoire; Ranchers -- Texas -- Basse vallée du Rio Grande -- Histoire; Mexicains -- Texas -- Basse vallée du Rio Grande -- Histoire; Basse vallée du Rio Grande (Tex.) -- Relations interethniques; HISTORY -- State & Local -- General; Ethnic relations; Frontier and pioneer life; Land tenure; Mexicans; Ranchers; Texas -- Lower Rio Grande Valley; Kolonisten; Frontier; Vie des pionniers -- Texas (États-Unis); Ranchers -- États-Unis -- Texas (États-Unis) -- Histoire; Propriété foncière -- Texas (États-Unis) -- Histoire; Mexicains -- États-Unis -- Texas (États-Unis) -- Histoire; Rio Grande, Vallée du -- Histoire; Texas (États-Unis) -- Relations interethniques; History